The Forces of Life and Death in Roch Carrier's Fiction - David J. Bond (Studies in 20th & 21st Century Literature, 1982)
Carrier's fiction is based on exaggeration and the grotesque, but it also deals with serious questions: the forces of life and death in the lives of his characters. Death is the subject of La Guerre, Yes Sir! and of several short stories, and it is symbolically present in certain other works. In Le Deux-millième étage and II est par là, le soleil, life in the city is equated with death. None of Carrier's characters live happy lives, and their religion is one of death and sin. As French-Canadians, they are threatened with destruction by the English-speaking world and by American capitalism. Yet they affirm their will to live by clinging to life; they react against their religion of death by blaspheming, and, in some cases, by openly rejecting it. They express their will to live through their sexual activity and by their humour. As a community, they show their will to survive by remembering their past. Jean-Thomas in II n'y a pas de pays sans grand-père, by talking of the past, keeps it alive and passes on to his grandson the will to survive as a French-Canadian. Telling stories which others will remember is thus a way of cheating death.
Keywords: Roch Carrier; life; death; dying; La Guerre; Yes Sir; Le Deux-millième étage; II est par là le soleil; sin; capitalism; humor; past; Jean-Thomas; II n' y a pas de pays sans grand-père; story telling